Menghadapi Tantangan dalam Pelayanan Publik, pada Badan Pendapatan Daerah Kota Pekanbaru - Sekar Mahalah; Bana Walifah (Universitas Sains dan Teknologi Komputer, 2023)
Agencies engaged in the field of public services under the government, especially in paying taxes, should provide good performance and service, so as to provide good organizational effectiveness as well, bearing in mind that taxes are one of the major revenues of the State. Where, if the government improves services in paying taxes, it will increase public interest in paying taxes.